Herpes Zoster Ophtalmicus : A case report - Meysandra, Puput Sagita (CV. Publikasi Indonesia, 2025)
Herpes zoster is infectious disease caused by reactivation of latent varicella zoster virus. Herpes zoster oftalmicus (HZO) will presented moderate to severe eye problem and visual loss. HZO resulting trigeminal nerve-related effect such unilateral rash and Hutchinson’s sign. We presented a case of herpes zoster oftalmicus to describe its clinical features and treatment. A 59 years old patient initially reported blurry vision, headache, eye discomfort and multiple lesion on right side face. At the first visit the visual acuity 5/30 on right eye and 5/12 on left eye. The patient was diagnosed herpes zoster oftalmicus gived antiviral treatment, articial tears and steroid topical eye drops. After 8 weeks treatment, the best corrected visual acuity was 5/12. Herpes zoster oftalmicus clinical features in older age patient as unilateral dermatome rash of trigeminal nerve. Treatment approaches widely for reduce risk of complication.